PENGARUH PENGELOLAAN KEUANGAN DAN SISTEM INFORMASI AKUNTANSI TERHADAP TRANSPARANSI KINERJA KEUANGAN BUMDES - Devi R. Wijaya; Fiany P. Shanda, Firdha A. Putri, Aditya F. Riansyah; Anita N. Andriyanto, Fanny A. Rahmasari, Vina Rustandy; Daniel Nababan, Romanus R. Sinaga, Vabian Reynaldi, Harry C. Adi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to determine the effect of financial management variables and accounting information systems on financial performance transparency variables. The research was conducted using qualitative methods and using a case study approach, and samples were taken from 32 respondents. This research was conducted in BUMDes Sauyunan, Cihideung Village, Parongpong District, West Bandung Regency with the aim of increasing understanding in managing BUMDes finance through the System Information Accounting. Hypothesis testing in this study using SPSS tools. The results showed that the Financial Management variable (X1) had no effect on the Financial Performance Transparency variable (Y), while the Accounting Information System variable (X2) had an effect on the Financial Performance Transparency variable (Y).